Fuzzy C-Means Clustering for Customer Segmentation - I Made Dhanan Pradipta; Agus Eka Anwar Wahyudi; Sri Aryani (International Journal of Engineering and Emerging Technology, 2018)
The right marketing strategy for a company canincrease revenue for the company. A product will not be boughteven known if the product sold is not clear its usefulness.Therefore, market segmentation is used to predict marketdemand based on market groupings such as Measurability(buyer characteristics and characteristics), Accestability(segmentation selected by company) and Substantiability (largesegment and profitable to serve).Customer segmentation is usedto determine the status of potential customers to choose the rightmarket strategy for the company. Clustering method used isfuzzy c-means, this method is determined based on the existenceof each data point by the degree of membership. Segmentationusing this clustering method will generate customer labels such assuperstar, golden, typical, occasional, everyday, and dormant.